Effects and mechanisms of probucol on aging-related hippocampus-dependent cognitive impairment - Yaru Xie (Elsevier, 2021)
Background: In the present study, we aimed to investigate the effects of probucol on aging-related hippocampus-dependent cognitive impairment and explore the potential mechanisms. Methods: D-galactose (100 mg/kg, once daily for 6 weeks) was subcutaneously injected to induce aging in mice. Then the mice were administered with probucol or vehicle once a day for 2 weeks. The hippocampus-related cognition was evaluated with Morris water maze test, novel object recognition test, and contextual fear conditioning test. Moreover, synaptic plasticity was assessed, and RNA-sequencing was applied to further explore the molecular mechanisms. Results: Aging mice induced by D-galactose showed conspicuous learning and memory impairment, which was significantly ameliorated by probucol. Meanwhile, probucol enhanced the spine density and dendritic branches, improved long-term potentiation, and increased the expression of PSD95 of aging mice. Probucol regulated 70 differentially expressed genes compared to D-galactose group, of which 38 genes were upregulated and 32 genes were downregulated. At last, RNA-sequencing results were verified by quantitative reverse transcription-polymerase chain reaction. Conclusions: Probucol improved learning and memory in aging mice through enhancing synaptic plasticity and regulating gene expression, indicating the potential application of probucol to prevent and treat aging-related disorders.